INTERPOLASI DATA BERDIMENSI d>1 DENGAN FUNGSI BASIS RADIAL (RADIAL BASIS FUNCTION) - Hery Andi Sitompul; Tambos A. Sianturi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2020)
Radial Basis Function (RBF) is a method typically used to aproximate a function based on information data. A radial function is a real valued function whose depends only on the distance the data input and some fixed point ,called a centre point. Distance between some fixed point/centre and data input is usually Euclidean metric so that . Commonly types of Radial Basis Function using a to indicate a shape parameter to scale the input data of the radial centre. Since this method has been proven effective and flexsibel so that it has been widely used in engineering and science, so in this paper we will discuss how to use Radial basis Function to interpolate 2 dimension data. From the result of discussion it was found that this method was accurate to aproximate actual data or observation.